2-{[2,8-Bis(trifluoromethyl)quinolin-4-yl](hydroxy)methyl}piperidin-1-ium trichloroacetate: Crystal structure and Hirshfeld surface analysis - Wardell, James L.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (2018)
The asymmetric unit of the centrosymmetric title salt, C17H17F6N2O+C2Cl3O2 , comprises a single ion-pair. The hydroxy-O and ammonium-N atoms lie to the same side of the cation, a disposition maintained by a charge-assisted ammonium-N—HO(hydroxy) hydrogen bond [the Oh—Cm—Cm–Na (h = hydroxy, m = methine, a = ammonium) torsion angle is 58.90 (19)⁰]. The piperidin-1-ium group is approximately perpendicular to the quinolinyl residue [Cq—Cm—Cm–Na (q = quinolinyl) is 178.90 (15)⁰] so that the cation, to a first approximation, has the shape of the letter L. The most prominent feature of the supramolecular association in the crystal is the formation of chains along the a-axis direction, being stabilized by charge-assisted hydrogen-bonds. Thus, ammonium-N+ —HO(carboxylate) hydrogen bonds are formed whereby two ammonium cations bridge a pair of carboxylate-O atoms, leading to eightmembered {OHNH}2 synthons. The resulting four-ion aggregates are linked into the supramolecular chain via charge-assisted hydroxyl-O—HO(carboxylate) hydrogen bonds. The connections between the chains, leading to a three-dimensional architecture, are of the type C—X, for X = Cl and F. The analysis of the calculated Hirshfeld surface points to the importance of XH contacts to the surface (X = F, 25.4% and X = Cl, 19.7%) along with a significant contribution from OH hydrogen-bonds (10.2%). Conversely, HH contacts, at 12.4%, make a relatively small contribution to the surface.